The Role Of Women Chief Executive Officers On Tax Avoidance Decisions In Islamic Stock Index - Wahid Wachyu Adi Winarto; Amalia Fakhru Nisa (JAS (Jurnal Akuntansi Syariah), 2023)
This study aims to show empirical data on the impact of women CEO traits on tax avoidance. The populations are all companies listed on the Indonesian Islamic Stock Index from 2021 to 2022, as many as 403 firms. The data collection technique used in this research was quota sampling, which obtained 350 observation data. The variables that were observed in this study were employed as the study's objectives, including the traits of women CEOs as independent variables, tax avoidance as a dependent variable, and profitability, leverage, and firm size as control factors. Multiple linear regressions are used in the analysis that was used to solve the first problem. The findings indicated that female leaders who serve as CEOs negatively influence tax avoidance. This research is expected to add to the literature and be helpful in the development of accounting disciplines, especially in corporate governance in disclosing tax avoidance by companies. The practical implications of this research provide helpful managerial implications for companies as corporate governance in managing strategies and policies related to corporate tax payments.